Location based routing addressing mechanism of integrated satellite and terrestrial network - Hewu LI; Lixin LIU; Jun LIU; Qian WU (Tongxin xuebao)
The ever-changing characteristics of the connection between the satellite network and the terrestrial network caused by the high-speed movement of the satellites have always been one of the most important problem that plagues the routing mechanism of the satellite network and integrated network.To address this problem,a location addressing based routing mechanism of integrated satellite and terrestrial network (LA-ISTN) was proposed.LA-ISTN exploited the user’s physical location in the user’s IP address to calculate the routing orientation.Based on the orientation,LA-ISTN could choose the best forward interface.Theoretical analysis and simulation experiments show that compared with snapshot protocol and OSPF routing protocol,LA-ISTN significantly reduces the route table storage overhead,with no routing updates cost caused by neighbor packet switching and communication.Inter-satellite route selection is not dependent on the prediction of link connection relations,with strong robustness,can always guarantee the network’s availability.